Studi Potensi Geowisata di Wilayah Danau Poso dan Sekitarnya Provinsi Sulawesi Tengah Menggunakan Analisis Spasial - Qodri, Muhammad Fatih; Lasawedi , Alifian Syahreza (Retii, 2023)
Lake Poso is one of the third deepest lakes in Indonesia and is located in Poso Regency, Central Sulawesi, and is one of the national priority lakes with all its characteristics and problems. The process of forming Lake Poso is part of the formation of Sulawesi Island. Has the characteristics of an ancient lake between 1-30 million years old. The result of this long geological process produces a variety of complex geological conditions that make the research location attractive from a scientific and tourism point of view. The research aims to examine the potential of geotourism in Lake Poso and its surroundings in Central Sulawesi Province. Geotourism involves exploring the geological and geomorphological features of an area, which can offer visitors a unique recreational and educational experience. By utilizing spatial analysis techniques, this study aims to identify and map the main geosites and geological features that have the potential for geotourism development. The analysis draws on multiple sources of spatial data, including topographic maps, satellite imagery and geological information. Geographic Information System (GIS) software is used to process and visualize this data set. Through the integration of geological, topographical and environmental data, important geosites such as mountains, caves, waterfalls and other typical landforms can be determined. The results of this research can become the basis for geotourism planning and sustainable development in the region. This research contributes to a broader understanding of the potential of geotourism to drive economic growth while promoting the conservation of natural and cultural heritage